Long-term survival of patients with CLL after allogeneic transplantation: A report from the European Society for Blood and Marrow Transplantation - Van Gelder, M.; De Wreede, L. C.; Bornhaeuser, M.; Niederwieser, D.; Karas, M.; Anderson, N. S.; Gramatzki, M.; Dreger, P.; Michallet, M.; Petersen, E.; Bunjes, D.; Potter, M.; et al. (Bone Marrow Transplantation, 2017)
Even with the availability of targeted drugs, allogeneic hematopoietic cell transplantation (allo-HCT) is the only therapy with curative potential for patients with CLL. Cure can be assessed by comparing long-term survival of patients to the matched general population. Using data from 2589 patients who received allo-HCT between 2000 and 2010, we used landmark analyses and methods from relative survival analysis to calculate excess mortality compared with an age-, sex- and calendar year-matched general population. Estimated event-free survival, overall survival and non-relapse mortality (NRM) 10 years after allo-HCT were 28% (95% confidence interval (CI), 25-31), 35% (95% CI, 32-38) and 40% (95% CI, 37-42), respectively. Patients who passed the 5-year landmark event-free survival (N=394) had a 79% probability (95% CI, 73-85) of surviving the subsequent 5 years without an event. Relapse and NRM contributed equally to treatment failure. Five-year mortality for 45- and 65-year-old reference patients who were event-free at the 5-year landmark was 8% and 47% compared with 3% and 14% in the matched general population, respectively. The prospect of long-term disease-free survival remains an argument to consider allo-HCT for young patients with high-risk CLL, and programs to understand and prevent late causes of failure for long-term survivors are warranted, especially for older patients.
CRIS-Team Scopus Importer:2023-03-23